The difficulty of reconciling the imperative of control and monitoring by the employer and respect for the privacy of the employee, in the face of digital technologies. French and Moroccan law - EL GDAIHI , Mohamed (Revue Internationale du Chercheur, 2021)
The purpose of this work is to draw a line between the exorbitant interventionism of employers and the vulnerability of wage earners, particularly with regard to the issue of privacy of the former and the excessive power of the latter. Even if the social courts in Morocco have not although had opportunity to give a ruling on conflicts relate to the question of the private life of the wage earner facing the sprawling powers of the employer in remote monitoring on the places of job; the moroccan judges will not contradict coherent legal and judicial standards and respected by french justice, since the moroccan law of 23 February 2009 relating to the protection of the individuals regarding the data processing with personal character strongly drew inspiration from the french model notably, the national committee of computer science and of freedom. In principle, the wage earner cannot be constantly monitored without his or her knowledge, and the employer can only achieve and exploit the employee's personal digital data in the presence of the employee for a serious and legitimate reason.